Dans Le Noir? Eating in the dark: sensation and conviviality in a lightless place. (October 2015) - Edensor, Tim; Falconer, Emily
Drawing on ethnographic interviews with customers, this paper looks at the experience of dining at Dans le Noir?, a restaurant in London where eating is carried out in complete darkness. As an exemplary gastro-tourist site within the expanding leisure economy at which sensory alterity is sought, we argue that the transformation of the usual unreflexive habits of sensing while dining offer opportunities to encounter difference and reflect upon our culturally located ways of sensing the world. In focusing upon the altered experience of apprehending space, eating and socialising in the absence of light, we contend that this dining experience offers broader suggestions about how we might reconsider the qualities and potentialities of darkness, a condition which has been historically feared and reviled in the west.